Identificación del mal funcionamiento y rediseño del sistema de potabilización y desinfección de agua potable regional los galtes parroquia matriz, del cantón Guamote provincia de Chimborazo. - Quito Logroño, Cristhian Gualberto (2013)
This investigation determined the cause of the malfunction of water treatment system and drinking water disinfection in "Los Galtes" regional branch which consists in two separate operating systems: the Yaguachi system which covers almost 200 household connections, and the Yanarumi system that supplies to 70 domestic connections, these two systems are in the Palmira parish, Guamote canton, Chimborazo province.